Emotional intelligence and non-social cognition in schizophrenia and bipolar I disorder. Issue 1 (19th September 2016) - Frajo-Apor, B.; Kemmler, G.; Pardeller, S.; Plass, T.; Mühlbacher, M.; Welte, A.-S.; Fleischhacker, W. W.; Hofer, A.
Abstract : Background: The different patterns of Emotional Intelligence (EI) deficits in schizophrenia and bipolar I disorder are are not yet well understood. This study compares EI levels among these groups and highlights the potential impact of non-social cognition on EI. Method: Fifty-eight schizophrenia and 60 bipolar outpatients were investigated using the Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT) and the Brief Assessment of Cognition in Schizophrenia (BACS). Analyses of covariance were performed with adjustment for the BACS composite score. Results: Compared to bipolar subjects, schizophrenia patients showed significantly lower levels in both EI and non-social cognition. After adjustment for the BACS composite score, the difference in EI was lost. The mediation analysis revealed that differences between schizophrenia and bipolar patients in strategic EI are almost fully attributable to the mediating effect of non-social cognition. Conclusions: Our findings suggest that in both schizophrenia and bipolar patients EI is strongly influenced by non-social cognitive functioning. This has to be taken into account when interpreting MSCEIT data in comparative studies in serious mental illness and emphasizes the importance of cognitive remediation.